Unpacking Digital Shopping Happiness in Preloved Markets: Roles of Self–Brand Congruence and Emotional Resonance - Elia Ardyan; Alicia Stephanie Gunawan (Journal The Winners, 2026)
An increase in preloved fashion sales is certainly shifting the market, reflecting a changing consumer penchant for sustainable purchases, self-expression, and emotional health. Therefore, this study aimed to assess the role of hedonic motivation, self-brand congruence, and emotional resonance in the shopping happiness of Indonesian customers purchasing preloved items. Each variable was related to satisfaction in different ways and collectively provided insight into positive outcomes in the Indonesian market. A centralized method was used to conduct the study, collecting data via Google Forms from a sample of 179 individuals in different Indonesian cities to prepare for Partial Least Squares Path Modeling (PLS-SEM) analysis. The result shows that hedonic motivation has a positive and significant effect on self-brand congruence. This implies that customers with hedonic motivation experienced stronger compatibility with selected brands. Furthermore, self-brand congruence is shown to influence emotional resonance and shopping happiness positively. Consumers in the preloved market are also influenced by price or functional benefits, as well as emotional experiences and personal identity ties. This study enhances the theoretical comprehension of digital consumer happiness as both a model and construct, examining the variable as an affective and identity-based concept that surpassed the limits of customer pleasure and happiness.